Beyond Inhibition: A Dual-Process Perspective to Renew the Exploration of Binge Drinking - Lannoy, Séverine; Billieux, Joël; Maurage, Pierre (Frontiers in Human Neuroscience, 2014)
Binge drinking is a widespread alcohol-consumption pattern in youth and is linked to cognitive consequences, mostly for executive functions. However, other crucial factors remain less explored in binge drinking and notably the emotional-automatic processes. Dual-process model postulates that addictive disorders are not only due to impaired reflective system (involved in deliberate behaviours), but rather to an imbalance between under-activated reflective system and over-activated affective-automatic one (involved in impulsive behaviours). This proposal has been confirmed in alcohol-dependence, but has not been tested in binge drinking. The observation of comparable impairments in binge-drinking and alcohol-dependence led to the “continuum hypothesis”, suggesting similar deficits across different alcohol-related disorders. In this perspective, applying the dual-process model to binge drinking might renew the understanding of this continuum hypothesis. A three-axes research agenda will be proposed, exploring: (1) the affective-automatic system in binge drinking; (2) the systems’ interactions and imbalance in binge drinking; (3) the evolution of this imbalance in the transition between binge drinking and alcohol-dependence.